ANALISIS JARINGAN PIPA DISTRIBUSI AIR BERSIH PADA DAERAH PEMUKIMAN MENGGUNAKAN PROGRAM WATERCAD - Didik Purwantoro DAN Sinta Aristy M. Mori (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTThis research is aimed to show the ability of tube tissue system distributesclean water in Balikpapan City recently. The use of waterCAD software is one ofthe alternative programs to drive an element tube exchange to get a betterclean water distribution tissue.The data of the research are city population, topography photograph,skeletonize-model map and its equipment. The data then were used for the inputof waterCAD software. According to the output of the program, it shows that itshould be a change of tube elements to gain pressure standard 150-300 kPausing scenario management facility.The result analysis using waterCAD software shows that the capacity ofclean water distribution pipe at this time have not been able to suffice the cleanwater demand, in this condition, the water flow has average pressure -29.735,05kPa which is not appropriate with pressure standard. The alternative program tosolve this matter is the change of tube diameter to 400, 500, and 600 mm andtube material from Galvanized Iron and Steel. The pressure after the change is174,5 kPa. The computation dispute between waterCAD software and analyticcomputation is 0,71% for flow debit and 2,27% for pressure at node. The differenceshows that the waterCAD software has been thoroughly tested.Keywords: water demand, clean water distribution system, waterCAD program